The Effect of Employee Performance on the Quality of Administrative Services: Pengaruh Kinerja Pegawai Terhadap Kualitas Pelayanan Administrasi - Dwi Putri, Novia; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2022)
The purpose of this study was to determine and analyze the effect of employee performance on the quality of administrative services at the Tanggulangin District office, Sidoarjo Regency. The research method used is correlational quantitative research. The sampling technique was Accidental Sampling and the determination of the sample size using Isaac & Michael's table calculations amounted to 347 respondents. The results of data analysis obtained from the respondents' questionnaires indicate that there is an influence between employee performance and the quality of administrative services at the Tanggulangin District office, Sidoarjo Regency as evidenced by the partial test with the value of the independent variable obtained that (sig < a = 0.000 < 0.05). This result is also evidenced by a simple linear regression analysis test, the value obtained from a simple linear regression analysis of employee performance is 0.837. Multiple correlation coefficient test obtained a value of 0.716 or close to 1 so that there is a strong relationship between the independent variables and the dependent variable. Multiple Determination Test to get the results of R Square is 0.576. It means that the rise and fall of the dependent variable is influenced by the independent variable, namely 57.6%, while the remaining 42.4% is influenced by other variables outside the variables studied.